Model Pengembangan Bisnis Toserba Sunan Drajat melalui Pendekatan Business Model Canvas: (Studi di Toserba Sunan Drajat Banjarwati Paciran Lamongan) - Nor Maysari; Musbikhin Musbikhin; Karmuji (Al-Muzdahir : Jurnal Ekonomi Syariah, 2023)
The business model offered to develop a business is very varied with technological advances and the times. This requires companies or business people to continue to innovate in running their business. The process of business development can be done by measurement through several analyses, one of which is the Businesss Model Canvas analysis by combining nine elements that are the initial foundation of the business in its classification. This type of research uses qualitative research methods with a descriptive approach obtained through data collection from the process of observation, interviews, and documentation. While data analysis techniques are used using data education, data presentation, and conclusions. The purpose of the study is to answer, know, describe and analyze the problem formulation; 1) What is the business development model at Sunan Drajat Banjarwati Paciran Lamongan Department Store. 2) How is the concept of Business Model Canvas analysis strategy at Sunan Drajat Banjarwati Department Store, Paciran Lamongan. 3) How is the concept of SWOT analysis at Sunan Drajat Banjarwati Department Store, Paciran Lamongan. The analysis used with the Business Model Canvas analysis approach with nine indicators from an internal and external perspective. In addition, it is strengthened by SWOT analysis which is collaborated on the Business Model Canvas analysis at Sunan Drajat Department Store. The results of the study explained that Sunan Drajat Department Store is a modern retail business that doubles into several businesses, including distributors, franchises, white labels, e-commerce, marketplaces, to business to business. The Sunan Drajat Department Store has actually implemented a canvas model bussines in its development. This alternative strategy can be seen from the strengths and weaknesses that have been analyzed with the SWOT analysis strategy that has been collaborated on the Business Model Canvas analysis so that it provides opportunities and challenges for the Sunan Drajat Department Store to develop its business